2012
DOI: 10.1152/ajprenal.00381.2011
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of luminal membranes of LLC-PK1cells to ANG II induces dimerization of AT1/AT2receptors to activate SERCA and to promote Ca2+mobilization

Abstract: Using the PLC inhibitor U73122, PMA, and calphostin C, it was possible to demonstrate the involvement of a PLC¡DAG(PMA)¡PKC pathway in the stimulation of SERCA by ANG II with no effect on PMCA. We conclude that ANG II triggers SERCA activation via the luminal membrane, increasing the Ca 2ϩ stock in the reticulum to ensure a more efficient subsequent mobilization of Ca 2ϩ . This first report on the regulation of SERCA activity by ANG II shows a new mechanism for Ca 2ϩ homeostasis in renal cells and also for reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…We avoid using cell cultures after the 30 th passage for the different experimental conditions; these cells had adhered to the flask by the basolateral side, thus keeping their polarity, an important characteristic of this cell line [22, 23, 24, 25]. To ascertain the effects of L-tyr and L-dopa on the ATPase activity, cells were incubated with them in Hank’s solution (137 mM NaCl, 5 mM KCl, 0.8 mM MgSO 4 , 1 mM MgCl 2 , 0.33 mM Na 2 HPO 4 , 0.44 mM KH 2 PO 4 , 0.2 mM Tris-HCl and 20 mM Hepes 0.25 mM CaCl 2 , pH 7.4), alone, or in the presence of the LAT2 inhibitor (BCH) and the D 1 R antagonist (Sch 23390).…”
Section: Methodsmentioning
confidence: 99%
“…We avoid using cell cultures after the 30 th passage for the different experimental conditions; these cells had adhered to the flask by the basolateral side, thus keeping their polarity, an important characteristic of this cell line [22, 23, 24, 25]. To ascertain the effects of L-tyr and L-dopa on the ATPase activity, cells were incubated with them in Hank’s solution (137 mM NaCl, 5 mM KCl, 0.8 mM MgSO 4 , 1 mM MgCl 2 , 0.33 mM Na 2 HPO 4 , 0.44 mM KH 2 PO 4 , 0.2 mM Tris-HCl and 20 mM Hepes 0.25 mM CaCl 2 , pH 7.4), alone, or in the presence of the LAT2 inhibitor (BCH) and the D 1 R antagonist (Sch 23390).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies using isolated basolateral membrane fractions from pig kidney have demonstrated that Ang II stimulates the renal proximal tubule Na + -ATPase activity via PI-PLCb/PKC pathway [99,100] . It is widely known that intracellular Ca 2+ mobilization in proximal tubule cells leads to the activation of many Ca 2+ -dependent intracellular signaling pathways, including those associated with Na + reabsorption [101] . Ang Ⅱ microperfusion techniques in rabbit superficial segment of proximal tubules in vitro regulated Na + reabsorption via PKC and intracellular Ca 2+ [102] ; low concentrations of Ang Ⅱ inhibited membrane Ca 2+ -ATPase via AT1/AT2 receptors heterodimers and PKC in isolated fractions of basolateral membranes of proximal tubule, increasing cytosolic Ca 2+ concentration in proximal tubule cells [37,103] .…”
Section: Breaking Paradigmsmentioning
confidence: 99%
“…Ang Ⅱ microperfusion techniques in rabbit superficial segment of proximal tubules in vitro regulated Na + reabsorption via PKC and intracellular Ca 2+ [102] ; low concentrations of Ang Ⅱ inhibited membrane Ca 2+ -ATPase via AT1/AT2 receptors heterodimers and PKC in isolated fractions of basolateral membranes of proximal tubule, increasing cytosolic Ca 2+ concentration in proximal tubule cells [37,103] . Luminal Ang Ⅱ stimulates AT1/AT2 receptors heterodimerization that increases sarco/endoplasmic reticulum Ca 2+ -ATPase activity and promotes Ca 2+ mobilization in proximal tubule cells [101] . The intracrine/intracellular system is new paradigm.…”
Section: Breaking Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Improved calcium handling may, in turn, lead to improvements in diastolic and systolic function of the heart, improve vascular relaxation and may even improve proximal tubule function. 7,8 …”
mentioning
confidence: 99%